2018
DOI: 10.1002/ecs2.2528
|View full text |Cite
|
Sign up to set email alerts
|

Collapse of trophic‐niche structure in belowground communities under anthropogenic disturbance

Abstract: The niche concept is a central paradigm in ecology, but empirical evidence on how the niche structure of belowground communities is affected by ecosystem disturbance is lacking. Niche differentiation evolves due to stable coexistence of species in a community, suggesting that in unstable communities, the niches of species should largely overlap. Here, we test this prediction using empirical data on the trophic‐niche structure of several belowground collembolan communities of natural (forest and meadow) and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 59 publications
(99 reference statements)
1
23
0
Order By: Relevance
“…Variations in Δ 13 C values among Collembola species were more pronounced in rainforest and jungle rubber than in rubber and oil palm plantations. Korotkevich et al (2018) also found the interspecific (in contrast to intraspecific) variation in trophic niches of Collembola to be higher in natural (forest and meadows) than in disturbed habitats (pastures and lawns). Among the Collembola species studied Δ 13 C values of Pseudosinella sp.1 in rainforest, and Callyntrura sp.1 and Sphyroteca sp.1 in jungle rubber differed significantly from those of other Collembola species indicating that these species are able to exploit resources not available to the other Collembola species in the respective land-use system.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Variations in Δ 13 C values among Collembola species were more pronounced in rainforest and jungle rubber than in rubber and oil palm plantations. Korotkevich et al (2018) also found the interspecific (in contrast to intraspecific) variation in trophic niches of Collembola to be higher in natural (forest and meadows) than in disturbed habitats (pastures and lawns). Among the Collembola species studied Δ 13 C values of Pseudosinella sp.1 in rainforest, and Callyntrura sp.1 and Sphyroteca sp.1 in jungle rubber differed significantly from those of other Collembola species indicating that these species are able to exploit resources not available to the other Collembola species in the respective land-use system.…”
Section: Discussionmentioning
confidence: 79%
“…Notably, the narrow range was due to both the lack of high trophic level (predators, scavengers) and low trophic level species (primary decomposers, specialized lichen feeders). This may reflect the dominance of generalist species in the disturbed habitat of oil palm plantations ( Korotkevich et al, 2018 ). Nematode communities also indicated oil palm plantations to be the most disturbed of the four land-use systems studied ( Krashevska et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For spotted skunks, the loss of a central dietary resource may have triggered a clear increase in the isotopic diversity of prey items taken. Declines in primary resources often result in increased dietary niche width for generalist foragers as alternative resources are increasingly incorporated (Korotkevich et al., 2018; Svanback & Persson, 2004; Wilson & Turelli, 1986). This trophic plasticity might allow individuals to incorporate novel resources, which can result in population growth and increased density; similarly, loss of high‐quality resources can incur fitness consequences (Hobart et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Quantifying alterations in the position and shape of the niche over temporal or spatial scales can reveal otherwise hidden attributes contributing to population decline (Manlick et al., 2019; Rossman et al., 2016; Swanson et al., 2015; Yeakel et al., 2013). For example, reduced availability of critical resources might be evidenced by an increase in intraspecific variation in niche space for generalist species as alternative resources are used (Korotkevich et al., 2018; Svanback & Persson, 2004; Wilson & Turelli, 1986).…”
Section: Introductionmentioning
confidence: 99%